FRI0164 Local tuberculosis incidence affects the rate of positive conversion in the quantiferon®-tb gold test among patients receiving infliximab or ct-p13 therapy. (23rd January 2014) - Yoo, D. H.; Shevchuk, S.; Ramiterre, E.; Kovalenko, V.; Tee, M.; Tobias Arteaga, E.; Morales Olazabal, L.; Baranauskaite, A.; Bukauskiene, L.; Lim, M. J.; Lee, Y.-A.; Rednic, S.; et al.
Abstract : Background: Treatment with an anti-TNF agent can increase the risk of tuberculosis (TB) by reactivation of latent tuberculosis infection (LTBI) or new infection. Objectives: To identify the risk of positive conversion in the QuantiFERON ® -TB Gold in-tube (QTF) test in rheumatoid arthritis (RA) and ankylosing spondylitis (AS) patients receiving infliximab (INX) or CT-P13, an INX biosimilar, in 15 countries with various TB incidences Methods: Of 856 enrolled subjects, 501 patients (373 RA in 14 countries, 128 AS in 8 countries) with negative QTF at baseline plus at least one follow-up QTF test result after study drug exposure were monitored for a 62-week period. Patients received either CT-P13 or INX (3mg/kg in RA; 5mg/kg in AS) at weeks 0, 2, 6 and then every 8 weeks up to week 54. Countries were divided into four risk groups according to TB incidence, as listed in the 2011 WHO TB report: very low (0–24/100000 population), low (25–49), intermediate (50–99) and high (100–299). In prevalent countries (Bulgaria, Colombia, Lithuania, Korea, Peru, Philippines, Romania and Ukraine), QTF was performed at weeks 14, 30, 54 and 62. In countries with very low risk, at least one QTF was performed under the Investigator's decision. Results: Positive conversion of QTF was observed in 22.0% (110/501) of patients (RA 20.9% [78/373]; AS 25.0% [32/128]). The positive conversion rate increased with local TB incidence (very low 16.0%, low 15.9%, intermediate 21.0% and high 26.5%). Relative risk (RR) of positive conversion in intermediate and high vs. low and very low TB incidence countries was 1.59 (95% CI: 1.09–2.34). Among very low incidence countries, conversion was associated with non-white ethnicity (RR 3.13; 95% CI: 1.07–9.11). In low, intermediate and high incidence countries, positive conversion was observed in 11.8% of patients at week 14, 7.6% at week 30 and 6.0% at weeks 54–62. RA patients aged ≥65 years (RR 2.19; 95% CI: 1.28–3.74) or of non-white ethnicity (RR 2.21; 95% CI: 1.49–3.26) were more likely to undergo positive conversion. Amongst patients who had positive conversion, 57.7% (45/78) of RA patients and 62.5% (20/32) of AS patients received prophylactic TB medication. No patient developed active TB during treatment. After treatment with CT-P13 or INX, 4 patients (2 RA, 2 AS) with a negative QTF at baseline developed active TB. Conclusions: To reduce TB incidence in patients treated with anti-TNF agents, serial testing using QTF in the first year of anti-TNF treatment could be helpful in detecting LTBI patients who had a false negative result at baseline, especially in countries with intermediate or high incidence of TB. Disclosure of Interest: D. H. Yoo Consultant for: CELLTRION Inc., S. Shevchuk Grant/research support from: CELLTRION Inc., E. Ramiterre Grant/research support from: CELLTRION Inc., V. Kovalenko Grant/research support from: CELLTRION Inc., M. Tee Grant/research support from: CELLTRION Inc., E. Tobias Arteaga Grant/research support from: CELLTRION Inc., L. Morales Olazabal Grant/research support from: CELLTRION Inc., A. Baranauskaite Grant/research support from: CELLTRION Inc., L. Bukauskiene Grant/research support from: CELLTRION Inc., M. J. Lim Grant/research support from: CELLTRION Inc., Y.-A. Lee Grant/research support from: CELLTRION Inc., S. Rednic Grant/research support from: CELLTRION Inc., C. Ahn Consultant for: CELLTRION Inc., Speakers bureau: CELLTRION Inc., H. Kim Employee of: CELLTRION Inc., W. Park Consultant for: CELLTRION Inc.